IMPROVEMENT OF STEAM TURBINE NUCLEAR POWER PLANTS CONTROL SYSTEMS AND AUTOMATION TURBINE BUILDINGS EQUIPMENT OF RUSSIA NUCLEAR POWER PLANTS - I. Z. Chernomzav; A. D. Melamed; K. A. Nefedov; T. N. Rumjantseva (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Typical structure of closed-loop control for steam turbine К-1000-60/3000, designed and implemented by «Interavtomatika» at the unit 4 Kalinin NPP are shown. A wide range of tests confirmed execution of all the functions of control, protection and antifault control. Based on this structure were developed projects of electronic part control system for units K-1200-60/3000 Novovoronezh nuclear power station and the BN800 Beloyarsk nuclear power plant. For turbine 1200 MW of the Belarusian nuclear power plant is expected to use the same proven solutions, but on the basis of new VNIIA developments.